Kepribadian Tokoh Utama dalam Novel Pengantara Karya Kaksubak (Teori Humanistik Abraham Maslow) - Sri Wahyuni; Irwansyah (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by the researcher's interest and desire to know more about the personality of the main character in the novel Pengantara by Kaksubak which consists of five characters, namely Mahendra Ajie Permana, Jiran Syahidin Putra, Ihsan Saepul Hidayat, Rasya Julianto, and Karel Aloysius Ginting. The purpose of this study was to describe (1) the personality of the main character in the novel Pengantara by Kaksubak, (2) the factors that influence the personality of the main character in the novel Pengantara by Kaksubak. This study used descriptive qualitative method. The data source is the novel Pengantara by Kaksubak. The data collected is in the form of words or quotations. The results of this study are (1) the personality of the main character in the novel Pengantara consists of two types of personality, namely healthy personality (Metaneeds) and unhealthy (Metapological). The healthy personality (Metaneeds) shown by Kaksubak in his novel are the characteristics of trust, wise and kind, beautiful, energetic and optimistic, complete, fair and altruistic, brave, simple, and full of meaning. Meanwhile, the unhealthy personality (metapological) shown by Kaksubak in his novel includes distrust, cynical and skeptical, hateful and disgusting, vulgar and numb, loss of enthusiasm for life, passivity and pessimism, chaos and unpredictability, likes angry, unfair, and selfish, insecure and need help, very complex and confused, irresponsible, don't know the meaning of life, lose hope, and despair. (2) the factors that influence the main character's personality in the novel Pengantara by Kaksubak consist of two factors, namely internal and external factors. Factors that greatly influence the personality of the five characters are external factors that come from the family and school environment.